The Effect of Whole-Body Traditional and Functional Resistance Training on CAVI and Its Association With Muscular Fitness in Untrained Young Men - Zuo, Chongwen; Bo, Shumin; Li, Qing; Zhang, Li (Frontiers in Physiology, 2022)
Abstract: Background: Resistance training-induced changes in the muscle function is essential for the health promotion of the young and older, but the discrepancies of the effect of resistance training on arterial stiffness leads to the divergence regarding to the effect of resistance train-ing on cardiovascular health. What confuses our understanding in this field may be the follow-ing factors: external load (higher intensity vs lighter intensity), participants’ cardiovascular health, and arterial stiffness assessment measurement. The purpose of the present study was to investigate the effects of the whole-body traditional high-intensity versus functional low-intensity resistance training protocol on systemic arterial stiffness, and their association with muscular fitness components in untrained young men. Methods: In this randomized controlled trial, twenty-nine untrained young men (mean age about 22.5 years old) were randomized into a 6-week (3 sessions per week) supervised whole-body traditional high-intensity resistance group (TRT, n = 15) consisting of 4-5 sets of 12 repeti-tions (70%1RM, lower-repetitions) or a whole-body functional low-intensity resistance group (FRT, n = 14) with 4-5 sets of 20 repetitions (40%1RM, higher-repetitions) to volitional failure. The systemic arterial stiffness (cardio-ankle vascular index, CAVI) and muscular fitness com-ponents were assessed before and after the 6-week training program. Results: There was a significant decrease (pre-post) for CAVI only in FRT group (p < 0.05), but no significant difference was observed between two groups. In addition, the TRT and FRT groups showed equally significantly increased in maximal strength, muscular endurance and power (within group: both p < 0.01); however, the independent t test exhibited that the differ-ence between two groups in terms of change in maximal strength, muscular endurance and power were no significant (p > 0.05). Furthermore, the reduction in CAVI was negatively corre-lated with the increase in 1RM of bench press for all participants (r = -0.490, p < 0.01,). Conclusions: Using present criterion-standard assessments measurements demonstrates that CAVI was significantly reduced after 6-week functional resistance training with beneficial ef-fect on muscular fitness. Negative and significant association between CAVI and 1RM bench press indicated the cardiovascular health may be involved in the regulation of resistance training.